2015
DOI: 10.1016/j.exer.2015.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular cytoskeleton and junction proteins of endothelial cells in the porcine iris microvasculature

Abstract: Recently we reported studies of the iris microvasculature and its endothelial cells using intra-luminal micro-perfusion, fixation, and silver staining, suggesting that the iris vascular endothelium may be crucial for maintaining homeostasis in the ocular anterior segment. Here we present information regarding the intracellular structure and cell junctions of the iris endothelium. Thirty-seven porcine eyes were used for this study. The temporal long posterior ciliary artery was cannulated to assess the iris mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Iris arteries and veins originate from the outer limbus limits of the uvea and progress up on the inner iris bordered by the pupil. Plenty of anastomosis is found between arteries and veins [1], allowing nutrition and oxygen supply not only to the iris tissue but also to the anterior chamber of the eye, and therefore maintain intraocular homeostasis [2]. In mammals, the development of the eye is not final at birth.…”
Section: Introductionmentioning
confidence: 99%
“…Iris arteries and veins originate from the outer limbus limits of the uvea and progress up on the inner iris bordered by the pupil. Plenty of anastomosis is found between arteries and veins [1], allowing nutrition and oxygen supply not only to the iris tissue but also to the anterior chamber of the eye, and therefore maintain intraocular homeostasis [2]. In mammals, the development of the eye is not final at birth.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 8 9 ] We analyzed and found that claudin-5, claudin-9, and claudin-11 are highly expressed in the heart, and they have all been reported to be expressed in endothelial cells. [ 10 11 12 13 ] Although hypoxia has been found to disrupt tight junctions, especially claudin-5 in cerebral endothelial cells,[ 14 15 ] the effects of hypoxia on claudin-5, claudin-9, and claudin-11 in cardiac microcirculation have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Claudin-5 is generally believed to be the main claudin subtype in endothelial cells, and it plays a crucial role in the endothelial barrier. [ 10 11 ] Claudin-9 and claudin-11 have also been reported to be expressed in endothelial cells, and function as important tight junction proteins. [ 12 13 ] Hypoxia has been found to disrupt tight junction complexes, especially claudin-5, causing cerebral endothelial barrier dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells are the innermost component of blood vessels, and tight junctions (TJs) located at the most apical portion of their lateral membranes serve as gatekeepers for the endothelial paracellular pathway (Tsukita et al 2001;González-Mariscal et al 2008). Previous studies have shown that the vascular endothelium is crucial for maintaining homeostasis in the ocular anterior segment (Yang et al 2015). Treatment with fenofibric acid prevents the aberrant distribution of TJ proteins in rat retinal endothelial cells, which is a possible mechanism for reducing excessive permeability in diabetic patients (Roy et al 2015).…”
Section: Introductionmentioning
confidence: 99%